Estrutura de uma floresta ripária na Estação Ecológica do Caiuá, Diamante do Norte, PR, Brasil : Ribeirão Scherer. - Pereira, Giovana Faneco (2012)
The riparian forest of Ribeirão Scherer, located in the Ecological Station Caiuá and Biodiversity Corridor Caiuá-Ilha Grande, was inventoried by a phytossociological your tree component to detect floristic gradients and its flora comparisons with other areas of the region. Therefore, longitudinal and perpendicular analyzes were prepared to the long axis of the stream, of successional groups, of dispersal syndromes and floristic similarity. The study area is located between the coordinates 22 ° 35'-22 ° 37'S and 52 ° 49'-52 ° 53'W, city of Diamante do Norte, State of Paraná, and inserted in the Biome Mata Atlântica and Phytoecological Region Seasonal Semideciduous Forest. We sampled 72 plots of 15x10 m, divided into four blocks of 18 contiguous parcels, being included in the inventory tree individuals, living or dead standing, with girth at breast height greater than or equal to 15 cm. The 1356 living individuals sampled were distributed in 110 species, 79 genera and 35 families. Eight families concentrated 63.6% of the species inventoried, especially Leguminosae, Myrtaceae, Lauraceae, Meliaceae and Rutaceae. Eugenia and Ocotea were the greatest wealth of genera, with five species each, followed by Casearia, Cordia and Nectandra, with four each, and Campomanesia, Machaerium and Trichilia, with three each. The floristic similarity analysis indicated the highest similarity with the State Park Morro do Diabo, separating them from inventories in the area of Corridor Caiuá-Ilha Grande. The analysis demonstrated between blocks forming two separate groups, and, between the strips, the marginal strip grouped with the intermediate range while keeping the distal isolated. Although having been characterized distinct communities, the separation between blocks and strips show, respectively, a floristic gradient towards high-low and margin-interior. The low similarity found between the 72 plots of FFRS indicates a high species richness that in areas of riparian vegetation, is related to the high heterogeneity of these environments. Metrodorea nigra A.St.-Hil., category dead, Astronium graveolens Jacq., Guarea kunthiana A.Juss., Crysophyllum gonocarpum (Mart. & Eichler ex Miq.) Engl., Aspidosperma polyneuron Müll.Arg., Alchornea triplinervia (Spreng.) Müll.Arg., Nectandra cuspidata Ness, Casearia gossypiosperma Briq. and Cabralea canjerana (Vell.) Mart. were the ten largest of VI and gathered 45.59% of the total. With respect to successional groups, was obtained floristic dominance and VI pronounced for the secondary, while the pioneers had low representation for both parameters. On the strategy of dispersion, zoochory dominated with 71 species, followed by anemochory with 28 and seven autocory. Changes in the composition and density of some species in the plots may be associated with the degree of disturbance in the area, mainly in the areas covered tracks and near the headwaters of the stream, due to increased brightness and microclimatic changes. Even though inserted into a UC, there is an urgent need to establish appropriate conservation practices, including protection against degradation factors such as fire and erosion processes against which the stream is being submitted Scherer gradually due to the edge effect. Management actions are essential to the conservation of species and the consequent maintenance of genetic diversity and biological FFRS to support future projects of rehabilitation of degraded areas in the northwestern region of Paraná, and especially Corridor Caiuá-Ilha Grande to which he belongs.